1992
DOI: 10.1007/bf00217126
|View full text |Cite
|
Sign up to set email alerts
|

Variation in gene copy number and polymorphism of the human salivary amylase isoenzyme system in Caucasians

Abstract: Summary. The polymorphic patterns of human salivary amylase of a large number of individuals of Caucasian origin were determined by using isoelectric focusing and polyacrylamide gel electrophoresis. Nine different salivary amylase protein variants were found; three of them are recorded for the first time and their heredity is shown. Some of the variants are encoded by haplotypes expressing three allozymes. Most variants display low frequencies. Analysis of the relative intensities of variant-specific isozyme b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…For example, a significant amount of variation in protein amount and activity was not explained by AMY1 gene copy number (R 2  = 0.25 and 0.27, respectively) in this study. Our finding is consistent with previous research [8], [9], which suggests that amylase expression may reflect additional genetic influences, such as nonsynonymous single nucleotide polymorphisms (SNPs) in the AMY1 gene (three known nonsynonymous SNPs) or differences in the transcription or translation efficiency between AMY1 genes in different haplotypes [9]. Furthermore, nongenetic influences, including stress and dietary starch intake, may additionally affect protein levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, a significant amount of variation in protein amount and activity was not explained by AMY1 gene copy number (R 2  = 0.25 and 0.27, respectively) in this study. Our finding is consistent with previous research [8], [9], which suggests that amylase expression may reflect additional genetic influences, such as nonsynonymous single nucleotide polymorphisms (SNPs) in the AMY1 gene (three known nonsynonymous SNPs) or differences in the transcription or translation efficiency between AMY1 genes in different haplotypes [9]. Furthermore, nongenetic influences, including stress and dietary starch intake, may additionally affect protein levels.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, there is evidence that salivary amylase expression is upregulated by a diet high in starch [7]. Genetically, salivary amylase levels are influenced by individual copy number variation (CNVs) of the AMY1 gene on chromosome 1p21, which codes for salivary amylase [8]. The AMY1 gene is one of the most variable CNV loci in the human genome, with a reported range of anywhere from 2 to 15 diploid copies.…”
Section: Introductionmentioning
confidence: 99%
“…Humans are unusual in that they have high levels of the salivary ␣-amylase, apparently due mostly to multiple copies of AMY1 genes. Among primates, multiple copy numbers of AMY1 genes have been identified only in H. sapiens (Groot et al 1989b;Bank et al 1992;Samuelson et al 1996). Furthermore, a strong correlation has been shown between AMY1 copy number and the concentration of amylase in saliva (Bank et al 1992;Perry et al 2007) as well as oral starch digestion rate (Mandel et al 2010).…”
Section: Salivary Amylasesmentioning
confidence: 99%
“…Among primates, multiple copy numbers of AMY1 genes have been identified only in H. sapiens (Groot et al 1989b;Bank et al 1992;Samuelson et al 1996). Furthermore, a strong correlation has been shown between AMY1 copy number and the concentration of amylase in saliva (Bank et al 1992;Perry et al 2007) as well as oral starch digestion rate (Mandel et al 2010). Young infants, prior to weaning in particular, who have a greater requirement for preformed glucose (Bier et al 1999) and for whom salivary amylases have greater importance in starch digestion , may have benefitted from multiple copies of the AMY1 genes.…”
Section: Salivary Amylasesmentioning
confidence: 99%
“…Such concept of constant gene copy-numbers is being gradually revised in the past twenty years, albeit unnoticeably. For examples, complement C4 and amylase manifest frequent and heritable gene copy-number variations among different healthy individuals (Bank et al , 1992;Blanchong et al , 2000;Carroll et al , 1984;Chung et al , 2002a;Dangel et al , 1994;Perry et al , 2007;Shen et al , 1994;Wu et al , 2007;Yang et al , 2003;Yang et al , 2007;Yang et al , 1999;Yu, 1991;Yu et al , 2003;Yu and Campbell, 1987). Recent advent of whole genome microarray studies and personal genomic DNA sequencing revealed numerous genomic loci with duplications of DNA segments > 1 kb in size; many of those segments contain protein-coding genes (Lupski, 2007;McCarroll, 2008;Redon et al , 2006;Sebat et al , 2004).…”
Section: Introductionmentioning
confidence: 99%